PERKAITAN ANTARA KONSEP KENDIRI DAN PENGINTEGRASIAN SOSIAL DALAM KONTEKS JENAYAH : SATU KAJIAN ULASAN SISTEMATIK (The Link between Self-Concept and Social Integration in the Context of Crime : A Systematic Review) - Tharshini, N. K.; Fauziah, Ibrahim (UTEM, 2019)
This article is prepared to review the link between self-concept and social integration in the context of crime. A systematic review was conducted to obtain information regarding the link between self-concept and social integration in databases such as Elsevier, Sage and Google Scholar. The results indicate that there is a significant relationship between selfconcept and social integration especially among individual who has involved in criminal activities. As an overall impact, the study provided implications to the concerned parties regarding the role of protective factors in order to reduce the recidivism rate.